Current data on the variability of the thigh muscles structure of athletes - Karatieieva , S.Yu.; Slobodyan , O.M.; Holovachuk , O.K.; Slobodyan , K.V.; Skoreyko , P.M. (Морфологія / Morphologia / Morfologìâ, 2024)
To be a professional athlete requires a high level of training, which, in addition to motor and functional abilities, must be supported by the appropriate morphological characteristics that differ in almost every sport, so the issue of sports selection is one of the most important components of the content of the work of a sports coach. Any coach wants to achieve the maximum possible result. At the same time, it should be remembered that nature has endowed us with different levels of abilities. It is important to learn to recognize them and take this into account in the practice of working with athletes. Taking into account the fact that the structure of the quadriceps muscle in athletes, its dimensions, especially during active training, places of attachment, shape, etc., which is important for sports selection and determination of sports orientation for team sports, is still insufficiently covered in literature sources. In our opinion, analyzing data from the literature, the ultrasound examination of muscles is accessible and informative, as it allows to determine the structure, shape, size and volume of muscles, places of attachment and existing pathologies or atypicalities. Such data are especially valuable when studying athletes at various stages of training, and are also of great importance when selecting athletes for a specific sport. So, the knowledge of the topographical and anatomical features of athletes' muscles is extremely important, since the volume, shape, and places of attachment of muscles make up a certain anatomical characteristic of an athlete of a specific sport, and also taking into account the fact that topographical and anatomical data about the muscular system of athletes is insufficiently described, therefore further research of the muscular system of athletes is relevant and important in sports practice.